Integrating river transport processes and seasonal dynamics to assess watershed nitrogen export risk - Jian Peng; Tianhan Lan; Jiabin Wang; Pei Xia; Huining Zheng (Environment International)
Excessive nitrogen exported to water bodies affects the balance of ecosystem and poses a threat to human health. Although the concept of water purification service helps quantify nitrogen export, the impact of river transport remains unclear. This study focused on nitrogen as a pollutant by utilizing the Integrated Valuation of Ecosystem Services and Tradeoffs (InVEST) model to assess nitrogen export in the Dongting Lake Basin, taking into account both the processes of sub-basin nitrogen export and river transport. Additionally, the monthly variations within the year were further explored, together with the identification of the priority area of returning cropland to forest land. The results showed that in 2021, the total nitrogen load outside the Dongting Lake was 11.34 × 108 kg·year−1, with the sub-basins retaining a total of 9.02 × 108 kg·year−1, accounting for 79.57 % of the total nitrogen load. Notably, the total nitrogen retention by the river made up 16.87 % of the total nitrogen retention, up to 1.83 × 108 kg·year−1. In view of monthly variation, water purification service based on the entire process was higher in winter and late autumn, and lower in summer and early autumn. The priority areas for ecological project were mainly distributed around the Dongting Lake, achieving an improvement of 58.15 % in water purification service with approximately 7.02 % of the total returnable cropland. This study proposed a new approach of water purification service assessment through integrating river transport processes and seasonal dynamics, aiming to assess watershed nitrogen export risk more accurately.